The Poverty of Strategy: E.P. Thompson, Perry Anderson, and the Transition to Socialism - Matthews, Wade (Labour/Le Travailleur, 2002)
Abstract The question of the transition to socialism has plagued Marxists since the 19th century. This paper investigates how two prominent British socialists in the 20th century — E.P. Thompson and Perry Anderson — sought to answer the question “What is to be done?” In doing so it provides a revision of conventional histories of the New Left, arguing that there was far more continuity between the “first” and “second” New Left than has conventionally been supposed. And it suggests that this becomes evident in a comparison between the socialist strategy of Thompson and Anderson in the early-to-mid 1960s.